General comparison of pre-chamber jet ignition and spark ignition on combustion and emission characteristics of a methanol direct injection engine - Hailiang Kou; Xiaodong An; Hao Duan; Xiaojun Yin; Ke Zeng (Case Studies in Thermal Engineering)
Compared with spark ignition (SI), pre-chamber jet ignition (PCJI) can effectively accelerate the combustion and extend lean burn limit. In this paper, the effects of PCJI and SI on methanol direct injection engine were investigated experimentally. Combustion comparison shows that PCJI can effectively shorten the ignition delay period and combustion duration. Especially under lean conditions with an excess air ratio (λ) being 1.3, PCJI can shorten the combustion duration by 45 % compared with SI. Lean burn limits and emissions are also improved. The λ limit for lean burn in SI mode is 1.4, while in PCJI mode it extends to 1.5. Under the lean condition with λ being 1.5, the BSHC and BSCO emissions in PCJI mode are reduced by 42.7 % and 27.6 %. The indicated mean effective pressure (IMEP) of PCJI exhibits lower sensitivity to spark timing (ST), through the co-optimization of λ and ST, the trade-off between engine performance and NOx can be improved.